Perkembangan Awal Pendidikan Islam diusantara - Halimah Soewandi Putri; Dinda Putri Somantri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of this study is to examine the development of Islamic education in the Nusantara from its traditional roots to the modern era, and to explore the key factors that have influenced changes in curriculum, teaching methods, and institutional reputation. This research employs a library-based method by reviewing historical records, academic literature, and scholarly journals related to the evolution of Islamic education in Indonesia. The findings indicate that the integration of religious sciences with general knowledge has strengthened the role of Islamic education in shaping individuals who are ethical, religiously grounded, patriotic, and capable of adapting to global challenges. The shift from classical learning models—such as meunasah, halaqah, and sorogan—to digitally driven and modern systems reflects a response to broader socio-cultural, economic, and political changes, including the influence of government policies during the New Order era. The study concludes that Islamic education in Indonesia holds a significant role in national civilization building, although challenges remain in terms of curriculum quality, institutional vision, educational facilities, and alignment with contemporary societal needs. Keywords: Education, Indonesia, Islam.